(untitled) (Quinto Sol, 2011)
This paper explores the activities that took place in the frame of the “Civic Action Plan¨ of the National Gendarmerie, in particular focusing on the creation and development of the “Gendarmería Infantil”. We hold that the plan aimed at integrating and improving the image of the Gendarmerie in the society, and that the experience of the Gendarmería Infantil was an attempt to influence on the socialization of children and youth by a sector of the military regime. The intention of influencing the education of youth and boys can be seen in the establishment of ties between them and security forces socialization values of these forces and participation in ceremonies strongly associated with its principles.